“They Didn’t Even Realize Canada Was a Different Country”: Canadian Left Nationalism at the 1971 Vancouver Indochinese Women’s Conference - Klein, Candice (Labour / Le Travail, 2019)
From 1 to 6 April 1971, over 600 women gathered to attend the Vancouver Indochinese Women’s Conference (viwc), an international women’s antiwar conference organized by women’s liberationists in Vancouver. The conference was intended to bring women together under the banner of an international sisterhood, but this desired goal did not happen. Instead, tensions between American and Canadian women divided conference organizers and attendees, culminating in verbal and physical conflict. The viwc is useful for examining how Canadian women experienced interactions with American feminists and radical activists in attendance at the conference. Several women viewed the actions of American delegates as imperialistic. The experiences of conference organizers and attendees show how the viwc represents a moment in women’s liberation where the limits to international feminism were particularly visible.